Role of Cover Crops in Improving Soil Health in Israel - Ban, David (American Journal of Agriculture, 2024)
Purpose: The aim of the study was to assess the role of cover crops in improving soil health in Israel. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that cover crops play a crucial role in enhancing soil health by improving its physical, chemical, and biological properties. These crops, typically planted during off-seasons when primary crops are not grown, help in preventing soil erosion, enhancing soil structure, and increasing organic matter content. Their root systems aid in breaking up compacted soil layers, thus improving aeration and water infiltration. Additionally, cover crops contribute to nutrient cycling by capturing residual nutrients, especially nitrogen, which might otherwise be lost through leaching. This not only reduces the need for synthetic fertilizers but also prevents nutrient runoff into water bodies, thereby protecting water quality. Cover crops also foster biodiversity within the soil by providing habitat and food for beneficial microorganisms and insects, which play a pivotal role in nutrient decomposition and pest management. Overall, the integration of cover crops into agricultural systems is a sustainable practice that promotes soil health, improves crop yields, and supports environmental conservation. Implications to Theory, Practice and Policy: Soil biota theory, resource capture theory and agroecological resilience theory may be used to anchor future studies on assessing the role of cover crops in improving soil health in Israel. Encourage farmers and land managers to integrate diverse cover crop species into their agricultural practices. Governments and agricultural agencies should implement policies that provide financial incentives, subsidies, or tax credits to farmers adopting cover crops.